2000
DOI: 10.1093/toxsci/54.2.441
|View full text |Cite
|
Sign up to set email alerts
|

Variable Pulmonary Responses from Exposure to Concentrated Ambient Air Particles in a Rat Model of Bronchitis

Abstract: Chronic bronchitis may be considered a risk factor in particulate matter (PM)-induced morbidity. We hypothesized that a rat model of human bronchitis would be more susceptible to the pulmonary effects of concentrated ambient particles (CAPs) from Research Triangle Park, NC. Bronchitis was induced in male Sprague-Dawley rats (90-100 days of age) by exposure to 200 ppm sulfur dioxide (SO2), 6 h/day x 5 days/week x 6 weeks. One day following the last SO2 exposure, both healthy (air-exposed) and bronchitic (SO2-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 34 publications
2
41
1
1
Order By: Relevance
“…Recently, this rat model of chronic bronchitis (CB) was used to study the effects of inhaled ambient particles (8,9) using the Harvard Ambient Particle Concentrator (HAPC). This device concentrates ambient outdoor particles in the fine particle range (0.1-2.5 µm) for subsequent direct delivery for animal exposure (10,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, this rat model of chronic bronchitis (CB) was used to study the effects of inhaled ambient particles (8,9) using the Harvard Ambient Particle Concentrator (HAPC). This device concentrates ambient outdoor particles in the fine particle range (0.1-2.5 µm) for subsequent direct delivery for animal exposure (10,11).…”
mentioning
confidence: 99%
“…This device concentrates ambient outdoor particles in the fine particle range (0.1-2.5 µm) for subsequent direct delivery for animal exposure (10,11). These studies demonstrated that concentrated ambient particles (CAPs) induced changes in pulmonary breathing parameters and elicited variable degrees of pulmonary inflammation (8,9).…”
mentioning
confidence: 99%
“…In the associations observed in this study between neutral sulfate and flow parameters (PEF and EF50), neutral sulfate concentrations ranged from 5.6 -139 g/m studies have not shown any association with sulfate. Indeed, while a number of CAPs studies in our laboratory and others have shown biological responses (Kodavanti et al 2000;Gurgiera et al 2002;Wellenius et al 2003;Urch et al 2004;Maciejczyk & Chen, 2005), these studies did not find associations between these effects and either measured sulfate or a sulfate factor. Kodavanti et al (2000) found that the leachable sulfate in CAPs from Research Triangle Park, NC, was not related to inflammatory responses in rats.…”
Section: Component-specific Resultsmentioning
confidence: 63%
“…Indeed, while a number of CAPs studies in our laboratory and others have shown biological responses (Kodavanti et al 2000;Gurgiera et al 2002;Wellenius et al 2003;Urch et al 2004;Maciejczyk & Chen, 2005), these studies did not find associations between these effects and either measured sulfate or a sulfate factor. Kodavanti et al (2000) found that the leachable sulfate in CAPs from Research Triangle Park, NC, was not related to inflammatory responses in rats. Increased activation of nuclear factor (NF)-κB in human bronchial epithelial cells did not correlate with sulfate from CAPs from the New York area (where sulfate constituted 65% of the PM mass) (Maciejczyk & Chen, 2005).…”
Section: Component-specific Resultsmentioning
confidence: 63%
See 1 more Smart Citation